AN INCENTIVE FOR RETAIL INVESTORS - Abrahão da Silva, Eudes; Salustiano, Ana Claudia; Theodoro, Jose Marcos Paula (Revista Interface Tecnológica, 2025)
The article shows how small investors who do not have specific knowledge of operating on the stock exchange can invest in solid companies. To do this, we present some academic concepts in finance, which can provide you with tools that can help you in decision making. Being able to invest resources in companies that maintain financial performance and profitability, heating up the stock market. It is observed that in the year 2022 there was a historic migration of Brazilians who invested in savings accounts and started investing in the stock market. It also presents the company WEG MOTORES S/A, a genuinely Brazilian company that is synonymous with financial security, it remained a leader on the stock exchange for 03 (three) consecutive years, specifically 2020, 2021 and 2022, with solid management, focused on seeking improvements continuous expansion of the industrial plant, seeking new markets and partnerships and a strong Governance and Compleice policy, which makes it a strong candidate to receive resources from these new investors Keywords: Small Investor. Stock Exchange. Profitability. Finance.